2015
DOI: 10.1039/c5ra00057b
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bending deformation on photovoltaic performance of flexible graphene/Ag electrode-based polymer solar cells

Abstract: Photovoltaic characteristics of flexible graphene/Ag electrode – based polymer solar cells as a function of electrode thickness under bending deformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…As an example, we used the PMMA/rosin-transferred monolayer graphene as an anode in flexible OPV cells (Figure a) with an active area of 0.2 cm 2 , which is larger than most of the relevant devices reported in the literature (Figure S12 and Table S2). , For comparison, we also fabricated and tested OPV cells under the same conditions, and of the same size and structure using a PMMA-transferred monolayer graphene film on PET or commercial ITO on glass as the anode. The cell made with PMMA/rosin-transferred graphene anode showed a higher short circuit current ( J SC ≈ 12.1 mA cm –2 ), open circuit voltage ( V OC ≈ 0.87 V) and fill factor (FF ≈ 54%) than those made with the PMMA-transferred graphene anode (Figure b,c and Table ).…”
Section: Resultsmentioning
confidence: 99%
“…As an example, we used the PMMA/rosin-transferred monolayer graphene as an anode in flexible OPV cells (Figure a) with an active area of 0.2 cm 2 , which is larger than most of the relevant devices reported in the literature (Figure S12 and Table S2). , For comparison, we also fabricated and tested OPV cells under the same conditions, and of the same size and structure using a PMMA-transferred monolayer graphene film on PET or commercial ITO on glass as the anode. The cell made with PMMA/rosin-transferred graphene anode showed a higher short circuit current ( J SC ≈ 12.1 mA cm –2 ), open circuit voltage ( V OC ≈ 0.87 V) and fill factor (FF ≈ 54%) than those made with the PMMA-transferred graphene anode (Figure b,c and Table ).…”
Section: Resultsmentioning
confidence: 99%
“…In 2015, Moaven et al reported the synthesis of an rGO/Ag nanocomposite electrode appropriate for OSCs [48]. The reported technique is applicable to flexible substrates by spin coating of an aqueous solution of rGO/Ag nanocomposite on polyethylene terephthalate (PET) substrate in ambient conditions.…”
Section: Chemically Treated Rgo Transparent Conductive Electrodesmentioning
confidence: 99%
“…Their applications in Dye Sensitized Solar Cells (DSSC) (Bella et al, 2015), energy storage and conversion (Griffini et al, 2014(Griffini et al, , 2013 have been reported recently. Encapsulation technology is widely used for various SPV technologies and systems such as Solar Thermoelectric (Sundarraj et al, 2014), silicon carbide (SiC) based SPV cells (Cheng et al, 2015), flexible polymer SPV cells (Moaven et al, 2015). Polymeric materials are most commonly used for encapsulation of c-Si SPV modules.…”
Section: Introductionmentioning
confidence: 99%